The Effect Of Public Service Motivation And Love Of Money On Employee Innovative Work Behavior - Ditta, Sarah (Politeknik Keuangan Negara STAN, 2023)
This study aims to examine the impact of public service motivation and love of money on innovative work behavior on work units at the Directorate General of Taxation, Ministry of Finance of the Republic of Indonesia. The research strategy for this study is a quantitative method with a survey as a data collection tool. The data sampling method is non-probability sampling with purposive sampling technique. The sample size is 254 respondents. Respondents are those who have status as Civil Servants in the Directorate General of Taxation and the minimum work period is 2 years. Data analysis using Partial Least Square - Structural Equation Model (PLS-SEM). The results of this study indicate that public service motivation and love of money have a positive effect on innovative work behavior.